Conversational Implicature on Youtobe Cianjur Said Azab With Netizen, 'Habib Jafar Stress' - Giri Hesty Utami; Yusni Khairul Amri (BIRCU, 2023)
Podcasts have recently been popular among celebrities and community leaders making podcasts or online conversations or interviews/dialogues with various groups that are currently viral. Figures that are considered viral are used as interview subjects so that the things that become viral are thoroughly and openly discussed by the hosts. The data used as an object on Deddy Combuzer's YouTube podcast, namely Habib Jafar, was used as the topic which was used as primary data for 1 hour 25 minutes of dialogue. After transcribing as many as 20 comments. This analysis is entitled Implicature YouTube Cianjur Dibilang Doom Sama Netizen, Habib Jafar Stress: In this study, the author uses a descriptive method which analyzes based on Grace's theory (2010) there are two types of implicatures. The results of the study concluded, the data used in this study are in the form of comments contained in the comments, the data is analyzed by steps (1) reading the comments contained on the YouTube social media, (2) marking each word or sentence that contains an implicature form (3) classifying based on types of implicature (4) conclude the data that has been presented carefully.